2019
DOI: 10.1155/2019/8028459
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Neuroendocrine Carcinoma of the Cervix in Pregnancy: A Case Report and Review

Abstract: Small cell neuroendocrine carcinoma of the cervix is a rare subtype of cervical cancer. Here we report a case in which a 27-year-old female patient presented at 34-week gestation with abnormal vaginal bleeding, underwent normal labor, and gave birth to a healthy neonate. Her pregnancy was complicated with a cervical tumor which turned out to be small cell neuroendocrine cervical carcinoma. We reviewed and discussed the features, diagnosis, and prognosis of small cell neuroendocrine carcinoma of the cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“… 6 17 In contrast to squamous cell cervical carcinoma which may allow for modest treatment delay due to pregnancy, immediate initiation of systemic treatment is recommended to improve maternal survival outcomes with the diagnosis of small cell cervical carcinoma. 5 16 19 In our case, chemotherapy was initiated in the second trimester to slow disease progression and preterm cesarean delivery was performed to allow earlier radiation therapy, affording our patient the best chance of prolongation of life.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 6 17 In contrast to squamous cell cervical carcinoma which may allow for modest treatment delay due to pregnancy, immediate initiation of systemic treatment is recommended to improve maternal survival outcomes with the diagnosis of small cell cervical carcinoma. 5 16 19 In our case, chemotherapy was initiated in the second trimester to slow disease progression and preterm cesarean delivery was performed to allow earlier radiation therapy, affording our patient the best chance of prolongation of life.…”
Section: Discussionmentioning
confidence: 95%
“…However, in patients diagnosed in pregnancy, caution must be taken to ensure that pregnancy is maintained and risk to fetal development is minimized. 4 5 6 Our case highlights the treatment course of a patient who was incidentally found to have small cell cervical carcinoma during a routine prenatal visit.…”
mentioning
confidence: 88%
“…Definitive diagnosis is made via biopsy staining for at least two neuroendocrine tumor markers such as synaptophysin, CD56, chromogranin, and NSE [ 5 ]. Misdiagnosis on imaging is common for cervical myomas or rapidly growing cervical polyps [ 6 , 9 ]. Treatment is currently limited due to the lack of sufficient research to date [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy regimens are based on those used in small cell lung cancer, consisting of cisplatin and etoposide [ 5 ]. With early diagnosis, the prognosis can be up to five years, but as little as one month if diagnosed in the later stages [ 9 , 10 ]. Poor prognosis has also been seen in smokers as well [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…General neoplasms are most often discovered in older individuals, but uterine cervical cancer is often detected in young patients. Pan et al 6 studied uterine cervical small-cell carcinomas that occurred during pregnancy, and the average age of their patients was 26.3 years. Those authors reported that over half of their patients with small-cell carcinoma during pregnancy died of that cancer.…”
Section: Discussionmentioning
confidence: 99%